The effect of trigona spp. Propolis extract to saliva substitute ph as xerostomia therapy - Cokro, Ingrid Aurelia Genacia; Priandini, Dewi; Pratiwi, Deviyanti; Hasan, Akhmad Endang Zainal (Odonto : Dental Journal, 2023)
Background: Patients with xerostomia generally have an acidic salivary pH. Low oral pH increases the occurrence of tooth caries and development of oral lesions such as recurrent aphthous stomatitis (RAS) which are prone to occur in patients with xerostomia. Trigona spp. propolis extract with antimicrobial compounds was used as an additional natural ingredient in saliva substitute to inhibit the growth of Streptococcus mutans and prevent the decrease of salivary pH in patients with xerostomia. This study aimed to determine the effect of Trigona spp. propolis extract to saliva substitute pH as therapy for xerostomia with antimicrobial activity. Method: This study was experimental laboratory, namely Post-test only Control Group Design. The propolis Trigona spp. extract used in this study was extracted using maceration method with 70% ethanol as solvent which was then diluted into 5 concentrations 1,25%, 2,5%, 5%, 10%, 20%. This study used Streptococcus mutans (ATCC 25175) and saliva substitute with pH of 6.8. The research includes phytochemical test, absorbance measurement and pH test. Result: There is a significant difference in the pH value between saliva substitute induced with Streptococcus mutans with Trigona spp. propolis extract and the control group. Data analysis using One-way ANOVA test showed a significant value of